Drivers of community turnover differ between avian hemoparasite genera along a North American latitudinal gradient. Issue 12 (9th June 2020) - Starkloff, Naima C.; Kirchman, Jeremy J.; Jones, Andrew W.; Winger, Benjamin M.; Huang, Yen‐Hua; Pulgarín‐R, Paulo C.; Turner, Wendy C.
Abstract: The latitudinal diversity gradient (LDG) is an established macroecological pattern, but is poorly studied in microbial organisms, particularly parasites. In this study, we tested whether latitude, elevation, and host species predicted patterns of prevalence, alpha diversity, and community turnover of hemosporidian parasites. We expected parasite diversity to decrease with latitude, alongside the diversity of their hosts and vectors. Similarly, we expected infection prevalence to decrease with latitude as vector abundances decrease. Lastly, we expected parasite community turnover to increase with latitudinal distance and to be higher between rather than within host species. We tested these hypotheses by screening blood and tissue samples of three closely related avian species in a clade of North American songbirds (Turdidae: Catharus, n = 466) across 17.5° of latitude. We used a nested PCR approach to identify parasites in hemosporidian genera that are transmitted by different dipteran vectors. Then, we implemented linear‐mixed effects and generalized dissimilarity models to evaluate the effects of latitude, elevation, and host species on parasite metrics. We found high diversity of hemosporidian parasites in Catharus thrushes ( n = 44 lineages) but no evidence of latitudinal gradients in alpha diversity or prevalence. Parasites in the genus Leucocytozoon were most prevalent and lineage rich in this study system; however, there was limited turnover with latitude and host species. Contrastingly, Plasmodium parasites were less prevalent and diverse than Leucocytozoon parasites, yet communities turned over at a higher rate with latitude and host species. Leucocytozoon communities were skewed by the dominance of one or two highly prevalent lineages with broad latitudinal distributions. The few studies that evaluate the hemosporidian LDG do not find consistent patterns of prevalence and diversity, which makes it challenging to predict how they will respond to global climate change. Abstract : Catharus thrushes are heavily infected by a diverse assemblage of hemosporidian parasites; however, these parasites did not follow a latitudinal diversity gradient or prevalence. Instead, we see high community turnover of Plasmodium communities with latitude and host species and moderate turnover of Leucocytozoon communities with latitude.